Assessment of the warranty period of a normal myocardial perfusion scintigraphy in patients with diabetes mellitus: 5 year follow-up of the prospective multicenter BARDOT trial. (8th February 2021) - Haaf, P; Caobelli, F; Haenny, G; Pfisterer, M; Zellweger, MJ
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Swiss National Foundation for Research Background: Asymptomatic diabetic patients with an abnormal myocardial perfusion scintigraphy (MPS) are known to be at an increased risk of major cardiac events (MACE) at 2-years follow-up. It remains unclear whether this finding holds true even for a follow-up of 5 years. Methods: four hundred patients with type-2 diabetes without coronary artery disease were evaluated clinically and with MPS and followed up for 5 years. Major adverse cardiovascular events (MACE) were defined as cardiac death, myocardial infarction or late coronary revascularization.  Results:  An abnormal MPS (SSS≥4 or SSS≥2) was found in 87 patients (21.8%). MACE within 5 years occurred in 14 patients with abnormal MPS (16.1%) and in 22 with normal scan (1.7%, p = 0.009); 15 deaths were recorded (3.8%). Patients with normal MPS had lower rates of MACEs than patients with abnormal scans (p = 0.016) (Figure 1A + B). Patients with abnormal MPS who had undergone revascularization had a lower mortality rate and a better event free survival from MI and revascularization than patients with abnormal MPS who had either undergone medical therapy only or could not be revascularized (Figure 1C + D).  Conclusions: Patients with  normal MPS have a low event rate and may not need retesting within 5 years (warranty period). Patients with an abnormal MPS have higher event rates and may benefit from a combined medical and revascularization approach.